2003
DOI: 10.1007/s11746-003-0835-5
|View full text |Cite
|
Sign up to set email alerts
|

NIR reflectance spectroscopic analysis of the FA composition in sesame (Sesamum indicum L.) seeds

Abstract: The feasibility of using NIR reflectance spectroscopy to estimate the FA composition of sesame seed (Sesamum indicum L.) samples from the National Institute of Crop Science of Japan and from Myanmar was examined. Multiple linear-regression analyses of NIR spectral data and chemical data for whole seeds were carried out to develop calibration equations for predicting the proportion of each of the four major FA in sesame seeds from the total FA composition. The SE of prediction (SEP) was 0.616% for palmitic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 16 publications
5
38
1
1
Order By: Relevance
“…The samples and the methods of chemical measurements were the same as those used in the previous report (Sato et al, 2003;Sato et al, 2004).…”
Section: Samples and Chemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples and the methods of chemical measurements were the same as those used in the previous report (Sato et al, 2003;Sato et al, 2004).…”
Section: Samples and Chemical Measurementsmentioning
confidence: 99%
“…The seeds need to be analyzed nondestructively for use in breeding and cultivation after the analysis and selection. We previously reported that the amounts of the major constituents and the fatty acid (FA) composition in plural sesame seeds could be successfully estimated by simple, rapid and nondestructive analysis using near infrared (NIR) spectroscopy (Sato et al, 2003;Sato et al, 2004). In this report, the nondestructive evaluation of sesame composition by using NIR spectroscopy was investigated for analysis of a small sample, i.e., single seed.…”
mentioning
confidence: 99%
“…These samples were sent to the National Agricultural Research Center for Kyushu Okinawa Region (KONARC, Kumamoto, Japan) for chemical and NIR analyses. The samples were the same as those used in the previous report (Sato et al, 2003).…”
Section: Samplesmentioning
confidence: 99%
“…NIR is also used for analyzing the fatty acid composition in sesame seeds (Sato et al, 2003) and for identifying their geographic origin by their contents (Kwon et al, 1998). The major constituents are important indices of seed quality for nutritional classifi cation, and their quantifi cation by NIR analyses would be valuable.…”
mentioning
confidence: 99%
“…Perez-Vich et al (1998) carried out a methodological study on the seed oil content and fatty acid composition of sunflower, and found that the accuracy when intact seeds were used was less than that for meal, but was sufficiently reliable for prescreening. Sato et al examined the feasibility of NIR spectroscopy for estimating sesame seed fatty acid (FA) composition, and reported that it was reasonably accurate for breeding purposes (Sato et al, 2003). Golebiowski (2004) and Golebiowski et al (2005) used NIR spectroscopy to investigate the oil in intact canola seed and discussed the attributes of the spectrum and the relationship between the principal components and the oil content.…”
Section: Introductionmentioning
confidence: 99%